PENGEMBANGAN MEDIA POP-UP BOOK CERBEL (CERITA FABEL) UNTUK MENINGKATKAN PEMAHAMAN UNSUR INSTRINSIK CERITA PADA SISWA KELAS IV - Hapsari, Yovita Diva; Rahmawati, Sajidda Andani; Sani, Fidela Amelia; Setiawaty, Rani (INOPENDAS: Jurnal Ilmiah Kependidikan, 2025)
This study aims to (1) develop Pop-up Cerbel learning media (2) determine the feasibility of Pop-up Book Cerbel learning media with intrinsic elements. This research design uses the ADDIE model. The place of this research was carried out at SD 04 Karangbener with the research subjects being grade IV students with a total of 17 students. This research was conducted in April-May 2024. Data collection techniques used observation, interviews, teacher and student responses and documentation. Researchers used pretests and posttests to determine the level of media effectiveness. The types of data in the form of qualitative and quantitative data were analyzed to obtain the product assessment feasibility category. The results of the study showed that first, the Pop-up Book Cerbel learning media with intrinsic story elements had been developed, second, the Pop-up Book Cerbel learning media received a feasibility score of 86.1% based on the results of the media expert validation test. Thus, the learning media in the form of Pop-Up Book Cerbel for grade IV passed the feasibility test and was used as a learning media that could improve the understanding of grade IV students at SD 04 Karangbener.